2005
DOI: 10.1099/vir.0.80760-0
|View full text |Cite
|
Sign up to set email alerts
|

Higher resistance of porcine trigeminal ganglion neurons towards pseudorabies virus-induced cell death compared with other porcine cell types in vitro

Abstract: Trigeminal ganglion (TG) neurons are important target cells for many alphaherpesviruses, constituting major sites for latency/reactivation events. Here, the in vitro kinetics of productive infection of the swine alphaherpesvirus pseudorabies virus (PRV) and resulting cell death in primary porcine TG neurons were determined, and these were compared with similar kinetics in many other porcine cell types. Confocal microscopy showed that all TG neurons expressed late genes such as viral glycoproteins, and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Furthermore, it was observed that surviving TG neurons (96 hours p.i.) were still able to transmit infectious virus to other cells (Geenen et al 2005). Other reports show that LAT can supress apoptosis (either in vivo or in vitro) and that this function may explain the importance of LAT in α-herpesvirus (for example HHV-1, BHV-1) latency and reactivation (Geiger et al 1995, Perng et al 2000, Jones 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was observed that surviving TG neurons (96 hours p.i.) were still able to transmit infectious virus to other cells (Geenen et al 2005). Other reports show that LAT can supress apoptosis (either in vivo or in vitro) and that this function may explain the importance of LAT in α-herpesvirus (for example HHV-1, BHV-1) latency and reactivation (Geiger et al 1995, Perng et al 2000, Jones 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Alphaherpesviruses, such as pseudorabies virus (PRV) and herpes simplex virus type 1 (HSV-1), have the ability to establish lifelong latent infection in sensory neurons innervating the primary site of replication (Geenen et al 2005). In vivo studies in natural host and mice indicated that EHV-1 replicates in the neurons of the trigeminal ganglion and the olfactory bulbs, where latent infection is also established (Awan et al 1990, Chesters 1997, Walker et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…However, cells infected with US3-negative PRV underwent apoptosis as measured by caspase-3 activation and terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling (TUNEL) assay for DNA fragmentation (143). US3-negative PRV also failed to prevent apoptosis in swine trigeminal ganglia neurons (142). Apoptosis was observed late in US3-null infected swine testicle cells (18-24 hours postinfection), suggesting that additional viral proteins may serve to inhibit apoptosis early in infection (143).…”
Section: Viral Antiapoptosis Genesmentioning
confidence: 99%
“…Neurons isolated from porcine trigeminal ganglia are more resistant to PRV-induced cell death than neurons isolated from the superior cervical ganglia and other porcine cell types. Trigeminal ganglia neurons survive productive PRV infection longer than other cell types, and this may extend the duration of infectious virus transmission during reactivation from latency (142). Several antiapoptosis genes have been implicated as modulators of apoptosis in HSV-1: UL54 (ICP27), US1 (ICP22), US3 (US3 PK), US5 (gJ), US6 (gD), RL2 (ICP34.5), and RL3 (LAT) (230).…”
Section: Viral Antiapoptosis Genesmentioning
confidence: 99%
“…While the HSV-2 Us3 null mutant spread from the cornea to the trigeminal ganglion via primary afferent neurons, subsequent viral spread was restricted compared to wildtype virus and correlated with an increased incidence of apoptotic cell death. The effects of Us3-deficient PRV have recently been investigated using porcine trigeminal ganglion cells (20,21). When these PNS neurons are productively infected by wild-type or Us3-deficient PRV, they become resistant to PRV-induced apoptosis compared to the responses of other cell types.…”
mentioning
confidence: 99%